Revisiting the integration of innovative methods of organizing students' individual work into the process of teaching a professionally oriented foreign language in a technological university - Ludmila Vladimirovna Chistobaeva (Вестник Майкопского государственного технологического университета)
Due to the implementation of the 3.0 University model, a technological university becomes an important structural component of the process of business development and technological entrepreneurship. The transfer of knowledge, characteristic of the 2.0 University model, is becoming insufficient, there is an objective need for a fundamental change in the traditional model of organizing student's individual work based on the integration of innovative teaching methods and a transdisciplinary approach.The research problem is integration of innovative methods of organizing independent study work in the process of teaching a professionally oriented foreign language.The purpose of the research is to reveal the potential of innovative methods for organizing individual work in foreign language teaching in a technological university.Method of selection, generalization and dissemination of advanced pedagogical experience have been used as the research methods.The results of the research are the following: the need to intensify students' individual work has been substantiated to fulfill the task of forming a given set of foreign language skills and abilities in accordance with the latest generation of the Federal State Educational Standards of Higher Education and the 3.0 University model; the potential of integration into the educational process of innovative methods of its organization has been proved.The key conclusions: individual work is an integral component of the process of teaching a professionally oriented foreign language at a technological university, the integration of innovative methods allows solving the problem of improving its quality, and also creates the prerequisites for implementing the principle of "lifelong education" and the transition to the 4.0 University model.